PKMζ Maintains Late Long-Term Potentiation by N-Ethylmaleimide-Sensitive Factor/GluR2-Dependent Trafficking of Postsynaptic AMPA Receptors - Yao, Yudong (Society for Neuroscience, 2008)
Although the maintenance mechanism of late long-term potentiation (LTP) is critical for the storage of long-term memory, the expression mechanism of synaptic enhancement during late-LTP is unknown. The autonomously active protein kinase C isoform, protein kinase Mζ (PKMζ), is a core molecule maintaining late-LTP. Here we show that PKMζ maintains late-LTP through persistent N-ethylmaleimide-sensitive factor (NSF)/glutamate receptor subunit 2 (GluR2)-dependent trafficking of AMPA receptors (AMPARs) to the synapse. Intracellular perfusion of PKMζ into CA1 pyramidal cells causes potentiation of postsynaptic AMPAR responses; this synaptic enhancement is mediated through NSF/GluR2 interactions but not vesicle-associated membrane protein-dependent exocytosis. PKMζ may act through NSF to release GluR2-containing receptors from a reserve pool held at extrasynaptic sites by protein interacting with C-kinase 1 (PICK1), because disrupting GluR2/PICK1 interactions mimic and occlude PKMζ-mediated AMPAR potentiation. During LTP maintenance, PKMζ directs AMPAR trafficking, as measured by NSF/GluR2-dependent increases of GluR2/3-containing receptors in synaptosomal fractions from tetanized slices. Blocking this trafficking mechanism reverses established late-LTP and persistent potentiation at synapses that have undergone synaptic tagging and capture. Thus, PKMζ maintains late-LTP by persistently modifying NSF/GluR2-dependent AMPAR trafficking to favor receptor insertion into postsynaptic sites.